Changes in the patterns of respiratory support and incidence of bronchopulmonary dysplasia; a single center experience - Saleh S. Algarni; Kamal Ali; Saif Alsaif; Nemer Aljuaid; Raghad Alzahrani; Maha Albassam; Rawan Alanazi; Dana Alqueflie; Maather Almutairi; Hessah Alfrijan; Ahmad Alanazi; Abadi Ghazwani; et al. (BMC, 2023)
Abstract Background With the advances in neonatal intensive care, the survival rate of extremely preterm infants is increasing. However, bronchopulmonary dysplasia (BPD) remains a major cause of morbidity among infants in this group. This study examined the changes in respiratory support modalities, specifically heated humidified high-flow nasal cannula (HHHFNC), and their association with BPD incidence among preterm infants born at < 29 weeks of gestation. Method This population-based retrospective cohort study included infants born at < 29 weeks of gestation between 2016 and 2020. Data regarding the use and duration of respiratory support modalities were obtained, including mechanical ventilation, continuous positive airway pressure, HHHFNC, and low-flow oxygen therapy. Additionally, the incidence of BPD was determined in the included infants. Trend analysis for each respiratory support modality and BPD incidence rate was performed to define the temporal changes associated with changes in BPD rates. In addition, a logistic regression model was developed to identify the association between BPD and severity grade using HHHFNC. Results Three Hundred and sixteen infants were included in this study. The use and duration of HHHFNC therapy increased during the study period. Throughout the study period, the overall incidence of BPD was 49%, with no significant trends. The BPD rate was significantly higher in the infants who received HHHFNC than in those who did not (52% vs. 39%, P = 0.03). Analysis of BPD severity grades showed that both grade 1 BPD (34% vs. 21%, P = 0.03) and grade 2 BPD (12% vs. 1%, P < 0.01) were significantly more common among infants who received HHHFNC than among those who did not. In contrast, the incidence of grade 3 BPD was lower in infants who received HHFNC (6% vs. 17%, P < 0.01). The duration in days of HHHFNC was found to significantly predict BPD incidence (OR 1.04 [95%CI: 1.01-1.06], P < 0.01) after adjusting for confounding variables. Conclusion The use of HHHFNC in extremely preterm infants born at < 29 weeks of gestation is increasing. There was a significant association between the duration of HHHFNC therapy and the development of BPD in extremely preterm infants born at < 29 weeks of gestation.